Gravity sensing, a largely misunderstood trigger of plant orientated growth - Lopez, David; Tocquard, Kévin; Venisse, Jean-Stéphane; Legué, Valerie; Roeckel-Drevet, Patricia (Frontiers in Plant Science, 2014)
Gravity is a crucial environmental factor regulating plant growth and development. Plants have the ability to sense a change in the direction of gravity, which leads to the re-orientation of their growth direction, so-called gravitropism. In general, plant stems grow upward (negative gravitropism), whereas roots grow downward (positive gravitropism). Models describing the gravitropic response following the tilting of plants are presented and highlight that gravitropic curvature involves both gravisensing and mechanosensing, thus allowing to revisit experimental data. We also discuss the challenge to set up experimental designs for discriminating between gravisensing and mechanosensing. We then present the cellular events and the molecular actors known to be specifically involved in gravity sensing.